In vivo targeted gene delivery to peripheral neurons mediated by neurotropic poly(ethylene imine)-based nanoparticles - Lopes, C (2016)
A major challenge in neuronal gene therapy is to achieve safe, efficient, and minimally invasive transgene delivery to neurons. In this study, we report the use of a nonviral neurotropic poly(ethylene imine)-based nanoparticle that is capable of mediating neuron-specific transfection upon a subcutaneous injection. Nanoparticles were targeted to peripheral neurons by using the nontoxic carboxylic fragment of tetanus toxin (HC), which, besides being neurotropic, is capable of being retrogradely transported from neuron terminals to the cell bodies. Nontargeted particles and naked plasmid DNA were used as control. Five days after treatment by subcutaneous injection in the footpad of Wistar rats, it was observed that 56% and 64% of L4 and L5 dorsal root ganglia neurons, respectively, were expressing the reporter protein. The delivery mediated by HC-functionalized nanoparticles spatially limited the transgene expression, in comparison with the controls. Histological examination revealed no significant adverse effects in the use of the proposed delivery system. These findings demonstrate the feasibility and safety of the developed neurotropic nanoparticles for the minimally invasive delivery of genes to the peripheral nervous system, opening new avenues for the application of gene therapy strategies in the treatment of peripheral neuropathies.